Granulomatous Scleromyxedema: Case Report and Literature Review. (March 2015) - Shlyankevich, Julia; Stetsenko, Galina Y.; George, Evan; Lantz, Dan M.; Burwick, Nicholas R.; Vary, Jay C.
Abstract : Abstract: Scleromyxedema is a rare and frequently disabling disease characterized by generalized waxy papules, skin induration, and cardinal histological features of dermal fibroblastic proliferation, thickened collagen, and mucin deposition. A monoclonal gammopathy is almost always present with rare progression to multiple myeloma. We describe the case of a 54-year-old man who presented with a rash in the setting of a new medication and histological features suggesting a granulomatous drug reaction. Despite discontinuation of the medication, the rash persisted and a second biopsy confirmed an interstitial granulomatous pattern. Serum protein electrophoresis identified the presence of a biclonal gammopathy leading to a diagnosis of granulomatous scleromyxedema. Review of the medical literature reveals only a handful of well-documented similar cases of this rare variant. It is important for pathologists and clinicians to be familiar with this condition to facilitate timely diagnosis and optimal clinical management of these patients.